Conflict Resolution of Remote Indigenous Communities (Overview of The Sociology Communication) - R Willya Achmad W (LEGAL BRIEF, 2021)
Conflict can be seen from two sides, it can be a weakness and a strength, the potential for conflict in remote indigenous communities is an old issue that cannot be resolved, conflict resolution from a sociological view of communication provides a new spirit that conflict can be controlled by means of interpersonal and intergroup approaches. This research method uses a literature study with a qualitative approach and data analysis using data reduction and data display. The results of the study explain that conflict resolution can work. When communicators approach traditional values ??that indigenous communities have and build trust between leaders, the dominant factor from the source of conflict is the struggle for power from the economy.